Modeling and simulation of logistics flows 1 - Réveillac, Jean-Michel (John Wiley & Sons, 2017)
Volume 1 presents successively an introduction followed by 10 chapters and a conclusion: A logistic approach. An overview of operations research. The basics of graph theory. Calculating optimal routes. Dynamic programming. Planning and scheduling with PERT and MPM. The waves of calculations in a network. Spanning trees and touring. Linear programming. Modeling of road traffic.